IMPLEMENTASI EKSTRAKURIKULER KEAGAMAAN DALAM MEMBENTUK KARAKTER SPIRITUALITAS SISWA DI MADRASAH ALIYAH TURUS PANDEGLANG - Mulya Herdiana; Budiana; Agus Hidayatullah (Jurnal Pendidikan Nusantara, 2024)
This study aims to analyse the implementation of religious extracurricular activities in shaping the spiritual character of students at Madrasah Aliyah Turus. The research questions in this study include: (1) how the implementation of religious extracurricular activities shapes the spiritual character of students; (2) what are the forms and types of religious extracurricular activities organised; and (3) what are the obstacles to their implementation. This study uses a qualitative method with a descriptive approach. Data collection techniques include observation, documentation, and interviews, while data analysis is carried out through four stages: data collection, data reduction, data presentation, and conclusion drawing. The results show that religious extracurricular activities play an important role in shaping the spiritual character of students through advice, encouragement, motivation, inspiration, and guidance, as well as the habit of good morals and the enforcement of discipline. In addition, these activities serve as a means of evaluating the development of students' character in their daily lives. These findings confirm that religious extracurricular activities have a significant contribution to the formation of spiritual character in the madrasah environment.